#TITLE_ALTERNATIVE# - PRAMUDITO (NIM: 12305013), DIMAS
The progression of time-lapse microgravity in surface to monitor fluide mass change caused by injection and production process in reservoir have been improving rapidly. The technology of borehole gravity help to identify massa change in reservoir. Using the mixed-determined linear inversion method between surface and borehole gravity, perhaps, it can investigate density change of fluide movement in reservoir. In my final project, forward modeling program is validated using GEOMODEL software while inversion modeling progam is tested using three synthetic models such as fault, single body, and complex model. Synthetic model is made in 3D geometry whose have mass dense certainly. Then, anomaly gravity response is used as inversion component. In this case, I use mixed determined inversion linear technique with damped least square factor as the important aspect to to minimize error length and solution length. Based on data processing, the forward modeling program is a good to apply in problem. Experiment to inversion program provide Lagrange number approximate 0.1. To get limit of error approximate 0.1 μGal, the program needs more thickness and width imitation model than synthetic model. Besides, application of joint inversion can investigate density change more detail and precision than both surface inversion and borehole inversion.